2020
DOI: 10.3847/1538-4365/ab789b
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Optical Monitoring of the Blazar S5 0716+714 from 2017 to 2019

Abstract: We continuously monitored the blazar S5 0716+714 in the optical g, r and i bands from Nov. 10, 2017 to Jun. 06, 2019. The total number of observations is 201 nights including 26973 data points. This is a very large quasisimultaneous multicolor sample for the blazar. The average time spans and time resolutions are 3.4 hours and 2.9 minutes per night, respectively. During the period of observations, the target source in the r band brightens from 14 m .16 to 12 m .29 together with five prominent sub-flares, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 101 publications
2
17
0
Order By: Relevance
“…Figure 1 shows the light curve; the measurement errors do not exceed the symbol size. The black crosses mark other published data (Raiteri et al 2003;Dai et al 2015;Ghisellini et al 1997;Hong et al 2017;Poon et al 2009;Liao et al 2014;Zhang et al 2008;Bhatta et al 2013;Wu et al 2012Wu et al , 2007Feng et al 2020;Xu et al 2019;Xiong et al 2020;Liu et al 2019). Our observations cover different periods of the object's activity.…”
Section: Observations and Light Curvesupporting
confidence: 71%
See 1 more Smart Citation
“…Figure 1 shows the light curve; the measurement errors do not exceed the symbol size. The black crosses mark other published data (Raiteri et al 2003;Dai et al 2015;Ghisellini et al 1997;Hong et al 2017;Poon et al 2009;Liao et al 2014;Zhang et al 2008;Bhatta et al 2013;Wu et al 2012Wu et al , 2007Feng et al 2020;Xu et al 2019;Xiong et al 2020;Liu et al 2019). Our observations cover different periods of the object's activity.…”
Section: Observations and Light Curvesupporting
confidence: 71%
“…The approximations by the linear function have a high Pearson correlation coefficient (≥ 0.975), so we consider it unreasonable to fit the observed dependences by a polynomial. Figure 3 displays the observed lines on the flux-flux diagram for a pair of R-V filters according to AZT-8 data, Dai et al (2015); Ghisellini et al (1997); Hong et al (2017); Liao et al (2014); Poon et al (2009); Wu et al (2007Wu et al ( , 2012; Zhang et al (2008); Raiteri et al (2003); Feng et al (2020); Xu et al (2019); Xiong et al (2020). The Figure 3 caption contains the time intervals considered in these references.…”
Section: Two Component Variability Modelmentioning
confidence: 99%
“…Despite that, Giommi et al (2008) combining Swift UVOT and XRT data, found evidence for 𝜈 peak variations in the IBL blazar S50716+714. Harder-when-brighter trends has been found in the infrared and optical part of the spectrum of the same object by Xiong et al (2020) and Morokuma et al (2020), suggesting that large 𝜈 peak variations should be present in IBL blazars as well.…”
Section: X-ray Emission In Blazars Of Different Types : Hbls Vs Ibls ...mentioning
confidence: 83%
“…The described change in δ would be reflected on the long-term light curve of the object, which would have prominent peaks. There are no such peaks on the observed light curve (e.g., Raiteri et al 2003;Dai et al 2013Dai et al , 2015Liao et al 2014;Yuan et al 2017;Xiong et al 2020). This could be explained by the fact that other peaks on the light curve are formed by physical processes, but then there is no enough evidence that variability caused by geometrical effects is not superimposed on changes in brightness that are the result of physical processes.…”
Section: Discussionmentioning
confidence: 99%